Cemeteries and gravemarkers : voices of American culture - Meyer, Richard E., 1939- (Utah State University Press, 1992)
Cemeteries house the dead, but gravemarkers are fashioned by the living, who record on them not only their pleasures, sorrows, and hopes for an afterlife, but also more than they realize of their history, ethnicity, and culture. Richard Meyer has gathered twelve original essays examining burial grounds through the centuries and across the land to give a broad understanding of the history and cultural values of communities, regions, and American society at large.